Critical route for coherent perfect absorption in a Fano resonance plasmonic system - Chong, Y. D. (2014)
We develop a method for realizing coherent perfect absorption in thin metamaterial systems, based on the coupled-mode theory of Fano resonance. Coherent perfect absorption refers to the complete absorption of symmetric plane waves incident on opposite sides of the system, due to critical coupling into the dissipative degrees of freedom. Using the reflection and transmission spectra measured on a limited number of samples, our theory predicts the precise frequency and metamaterial parameter values required to achieve coherent perfect absorption. The coupled-mode theory and the design method are found to agree well with full-wave numerical simulations of a subwavelength-thickness metamaterial surface with a pair of bright and dark plasmonic modes.